Chloropropanols (3-MCPD, 1, 3-DCP) from food contact materials: GC-MS method improvement, market survey and investigations on the effect of hot water extraction. Issue 6 (3rd June 2021) - Korte, Robin; Schulz, Susann; Brauer, Beate
ABSTRACT: The chloropropanols, monochloropropane-1, 2-diol (3-MCPD) and 1, 3-dichloro-2-propanol (1, 3-DCP) are potential contaminants that may be found in food contact materials (FCM) from paper and paperboard that have been treated with certain wet-strength resins. They can migrate from the paper matrix to aqueous food and beverages and, due to their potentially carcinogenic properties, are of increasing interest in quality assurance or official controls of paper-based FCM. We hereby describe an improved method for the analysis of 3-MCPD and 1, 3-DCP in water extracts of FCM making use of 1-chloro-3-methoxy-2-propanol (CMP) as a novel internal standard. The LOD and LOQ were determined to be 0.4 µg/L and 1.2 µg/L for both analytes, making the method appropriate for the quantification of 3-MCPD and 1, 3-DCP below the current legal limits. The method was applied to an extensive market survey of food contact articles made from paper and paperboard including 674 samples. The survey revealed that a high percentage of the products available on the market (e.g., up to 55% of the analysed drinking straws) exceed the BfR limits with values of up to 327 µg/L 3-MCPD and 20 µg/L 1, 3-DCP detected in the cold water extract. Remarkable differences were observed concerning the release of 3-MCPD and 1, 3-DCP from different kinds of paper-based FCM products, with drinking straws, cupcake cases, bagasse bowls and kitchen rolls showing particularly high rates (>10%) of non-conformity with the legal limits. A number of samples with especially high concentrations were additionally analysed by hot water extraction, which surprisingly yielded considerably lower results for the release of 3-MCPD and 1, 3-DCP than cold water extraction. The results indicate that cold water extraction is the most sensitive method to detect the migration and control the risk of exposure to 3-MCPD and 1, 3-DCP. Graphical Abstract: uf0001